Study of mathematical literacy ability of grade VIII students in solving PISA problems in view of gender - Turianda, Nanza; Jumaisyaroh Siregar, Tanti (Desimal: Jurnal Matematika, 2025)
This study aims to analyze the mathematical literacy skills of grade VIII students at MTS Darul Ilmi Batang Kuis in solving Programme for International Student Assessment (PISA) questions based on gender. This research used descriptive qualitative method. The research subjects consisted of 20 students, including 10 male students and 10 female students selected through purposive sampling. Data collection techniques include data reduction, data presentation, and conclusion drawing. The data analysis techniques used were tests, interviews, and documentation. This study used triangulation as a data verification technique. The problems used in this study were estimated to be at Level 3 (easy), Level 4 (medium), and Level 5 (difficult), and analyzed based on aspects of mathematization, communication, reasoning, and argument. Only two students (one male and one female) reached Level 3. The total score for the male student was 21, while the female student obtained a total score of 20, with the rest remaining at Level 2. Conclusion Analysis was conducted using the scoring rubric and interviews. On average, the results showed that male students' mathematical literacy skills were slightly higher compared to female students. This study recommends the importance of implementing learning strategies that take into account gender differences and strengthen students' understanding of contextualized mathematical concepts to improve overall mathematical literacy.